Threats from the East and the South as V4 Defence and Security Cooperation Catalysers - Jakub Kufčák (Vojenské rozhledy, 2015)
Recent developments in security environment in the last two years re-opened crucial European debates such as the reform of the NATO architecture to address resurgent Russia to the East and as finding common European solution to migratory pressures that test both national capabilities and European solidarity. Even through the Visegrád countries do not always share common interests, the V4 manifests that it can play indispensable role in reaction to these developments. However, V4 still lacks actually proactive regional approach that would accommodate polish interests in order to keep informal leader Poland invested in this cooperation format. Polish elections mean one more challenging test for the V4 to coordinate positions before the crucial NATO Warsaw summit. Should this endeavor be unsuccessful, Poland could look to other formats that mirror its interests and threat perception more closely meaning that V4 would take a back seat with regard to NATO agenda. The task for the Czech V4 presidency is to produce practical results in ongoing ambitious project in defence cooperation so that is demonstrates the cooperation’s ‘added value.